2017
DOI: 10.1111/ecc.12639
|View full text |Cite
|
Sign up to set email alerts
|

Independent psychometric validation of European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Endometrial Cancer Module (EORTC QLQ-EN24)

Abstract: The endometrial cancer (EC)-specific Quality of Life module of the European Organization for Research and Treatment of Cancer (EORTC QLQ-EN24), was developed and validated in one study. We independently validated and assessed the psychometric properties of the instrument. Two hundred and eight women with EC before surgery, during adjuvant treatment and follow-up; in three different cancer centres completed the EORTC QLQ-C30 and the EN24. The questionnaire's completion rate was 100%, except sexuality items, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
1
16
1
1
Order By: Relevance
“…The HRQL was also reported in many trials regarding adjuvant radiotherapy in endometrial carcinoma patients. The EORTC QLQ-C30 questionnaire to assess the HRQL was used in many well-known trials [10,17], but the EORTC QLQ-EN24 module for endometrial carcinoma patients is a relatively new tool with only a few trials reported recently [11,19]. In the PORTEC-1 trial, comparing the use of EBRT with no adjuvant treatment, EBRT was associated with long-term urinary and bowel symptoms and lower physical and role-physical functioning [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRQL was also reported in many trials regarding adjuvant radiotherapy in endometrial carcinoma patients. The EORTC QLQ-C30 questionnaire to assess the HRQL was used in many well-known trials [10,17], but the EORTC QLQ-EN24 module for endometrial carcinoma patients is a relatively new tool with only a few trials reported recently [11,19]. In the PORTEC-1 trial, comparing the use of EBRT with no adjuvant treatment, EBRT was associated with long-term urinary and bowel symptoms and lower physical and role-physical functioning [9].…”
Section: Discussionmentioning
confidence: 99%
“…The HRQL can be measured using validated questionnaires. In patients with endometrial carcinoma, it can be done with the European Organization for Research and Treatment of Cancer (EORTC) core quality of life questionnaire (EORTC QLQ-C30) with Quality of Life Questionnaire-Endometrial Cancer module (EORTC QLQ-EN24) [11][12][13]. In the EORTC QLQ-C30 questionnaire, response scales ranging from 1 to 4 points for all items except for items 29 and 30 with response scales from 1 to 7 points.…”
Section: Introductionmentioning
confidence: 99%
“… 47 A higher score reflects a better level of functioning and better QoL. Tumour-specific complaints are measured using the disease-specific supplements EORTC QLQ-EN24 49 for endometrial cancer, EORTC QLQ-OV28 50 for ovarian cancer, EORTC QLQ-CX24 51 for cervical cancer and EORTC VU-34 (under development, phase 4) for vulvar cancer. The EORTC instruments (except EORTC VU-34) have been used in studies of gynaecological cancer survivors, some of which were conducted in Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Penilaian kualitas hidup pasien dilakukan dengan wawancara dan mengisi kuosioner berdasarkan modul EORTC QLQ-C 30 dan QLQ-EN 24. 23,24,25 Subjek penelitian adalah faktor-faktor klinikohistopatologi sebagai faktor prognosis dari kanker endometrium yang dapat mempengaruhi kualitas hidup penderitanya. Penelitian dilakukan di RSUP dr. Sardjito Yogyakarta selama enam bulan yang dimulai sejak ethical approval diterbitkan.…”
Section: Metodeunclassified